Dementia : prevalence, risk factors and management strategies - Tanner, Pamela (Neurology--laboratory and clinical research development series., 2014)
"Dementia is a distressing, progressively disabling, financially burdening and, most of all, self-erasing illness. The nature of the disease presents patients, families and care providers from multiple domains with numerous, multi-faceted challenges. As a rule, these challenges morph into new and distinctive challenges as patients move through various stages of the disease. Caring for persons with dementia represents one of the most challenging medical issues of the 21st century. A sense of urgency related to the problem of dementia has recently intensified, as the number of patients receiving a new dementia diagnosis is rapidly on the rise. This book explores the prevalence, risk factors and the management strategies available for dementia patients."--